Kesulitan guru mengimplementasikan metode proyek dalam pembelajaran PPKn di Sekolah Menengah Kejuruan - Khanza Sabina Maharani; Al Rafni; Hasrul Hasrul; Monica Tiara (Journal of Education, Cultural and Politics, 2026)
This study aims to analyze the difficulties faced by teachers in implementing the project method and efforts to overcome these difficulties in implementing the project method in Pancasila Education learning at SMKN 4 Padang. This study uses a qualitative approach with a descriptive research design and was conducted at SMKN 4 Padang, located on Jl. Raya Padang - Indarung, Cangkeh Nan XX, Lubuk Begalung, Padang City, West Sumatra. Informants were selected using a purposive sampling technique, which involves self-identification of informants based on certain considerations or criteria in accordance with the research objectives. The research informants consisted of 21 people: the principal, curriculum representatives, facility and infrastructure representatives, Pancasila Education teachers of grades 10, 11, and 12, and five students of grades 10, 11, and 12. Data were collected through observation, interviews, and documentation studies. Data validity was tested using source triangulation techniques, while data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions which were carried out continuously from the data collection process until the research was completed, so that it could answer the research problem formulation precisely and in depth. The results of the study indicate that teachers face various difficulties in implementing the project method in Pancasila Education learning at SMKN 4 Padang. Difficulties in the planning stage lie in the teachers' ability to translate general learning outcomes into concrete projects, develop project learning plans, and design the division of tasks and activity stages that are appropriate to time, student abilities, and facility conditions. Teachers' efforts to overcome difficulties in evaluating the project method include simplifying and adjusting assessment instruments to be relevant and easy to understand, combining process and outcome assessments, and strengthening individual assessments for group equality. Teachers also manage time efficiently, increasing consultation and feedback.